Prehistoric human response to climate change in the Bonneville basin, western north America: The Bonneville Estates Rockshelter radiocarbon chronology. (15th May 2021) - Goebel, Ted; Hockett, Bryan; Rhode, David; Graf, Kelly
Abstract: The extent to which long-term climate change has influenced cultural evolution among hunter-gatherers has long been debated. In the Great Salt Lake desert (USA), a detailed record of paleoenvironmental change has been developed for the last 15, 000 years, but a similarly complete chronicle of human occupation and adaptation is less secure. Here, we report and analyze one of the largest datasets (n = 247) of radiocarbon ages yet amassed from a single archaeological site in the Americas — Bonneville Estates Rockshelter, Nevada — to investigate human-environment interaction in this desert setting since 13, 000 years ago. Results show a striking consistency in human-occupation intensity and oscillations between cool, mesic and warm, arid climate, specifically high occupation intensity during relatively cool times, and low intensity — even abandonment — during extended periods of drought. The ultimate outcome is a clear case of how long-term oscillations in climate can repeatedly motivate change in foraging societies in a marginal environmental setting. Highlights : Rare glimpse of human prehistory 13, 000 years ago to historic times in ancient cave. Proxy records of paleoenvironment and human prehistory joined in Bonneville basin USA. One of the most precise and protracted archaeological chronologies in North America. Archaeological chronology of the eastern Great Basin revised with new excavation. Long-term climate change repeatedly motivated evolution in human foraging societies.